Resurgence of African Spiritualities in the New Prophetic Churches - Resane, Kelebogile Thomas (Pharos Journal of Theology, 2024)
The current developments in New Prophetic Churches (NPCs) raise the necessity for theological research. There are some practices within these formations, similar to African spiritualities. Spirituality is defined and some reflections on African spiritualities highlighted. This article identifies the NPCs and African spiritualities and how the two converge towards spiritual formation for Christians in these churches. Literature review and social media are used to research and conclude the research question, which is the resurgence of African spiritualities in faith formation of this faith community. Justification for this resurgence is based on both theological and etymological analyses of features, especially occultism and deliverance. Research finding is that many believers abandon Christian faith or opt to be opponents of the Gospel when promised prophecies are not fulfilled. Hence a conclusion is arrived at as an appeal for the return to Christian apologetics and vivacious socio-cultural contextual studies in the church. Robust dialogue with NPC leaders is long overdue, as at the end the local pastors are the ones engaged with damage control after the prophet has passed. Minimum standards should be suggested to minimize emotional damage in individuals and communities of faith, and discipleship into Christian faith needs to be heightened.
free